Grasp the correct diagnostic approaches and methods of dizziness and vertigo: interpretation and enlightenment from "Multidisciplinary expert consensus of diagnosis and treatment of vertigo" - Yan-sheng LI (Chinese Journal of Contemporary Neurology and Neurosurgery, 2018)
Dizziness and vertigo are common clinical conditions with complex and overlapped clinical features that caused by various disorders and diseases. Therefore, it is important to grasp the correct diagnostic approaches and methods. First, it is necessary to carry out a careful history inquiry to understand the nature and type, duration, accompanying symptoms and related medical history. The second is to carry out careful neuro -otological examinations and targeted tests. The indiscriminate auxiliary examination does not help the diagnosis. Based on the above process, the diagnosis of different vestibular syndromes (acute, episodic or chronic) can be realized, and the diagnosis of disorders or diseases can be made according to diagnostic criteria. The paper discussed how to make the final diagnosis by inquiry and physical examination, auxiliary examination and syndrome diagnosis on the basis of "Multidisciplinary expert consensus of diagnosis and treatment of vertigo".